Evolution of social conflict in the bacterium Myxococcus xanthus: centimeter vs global scale populations - Vos, Michiel (2009)
Social interactions among microbes that engage in cooperative behaviours are well studied in laboratory contexts [1, 2], but little is known about the scales at which initially cooperative microbes diversify into socially conflicting genotypes in nature. The predatory soil bacterium Myxococcus xanthus responds to starvation by cooperatively forming multi-cellular fruiting bodies in which a portion of the population differentiates into stress-resistant spores [3, 4]. Natural M. xanthus populations are spatially structured [5] and genetically divergent isolates from distant origins exhibit striking developmental antagonisms that decrease spore production in chimaeric fruiting bodies [6]. Here we show that genetically similar isolates of M. xanthus from a centimeter-scale population [7] also exhibit strong and pervasive antagonisms when mixed in development. Negative responses to chimerism were less intense, on average, among local strains than among global isolates, although no significant correlation was found between genetic distance at multi-locus sequence typing (MLST) loci and the degree of social asymmetry between competitors. A test for self/non-self discrimination during vegetative swarming revealed a great diversity of distinct self-recognition types even among identical MLST genotypes. Such non-self exclusion may serve to direct the benefits of cooperation to close kin within diverse populations in which the probability of social conflict among neighbours is high.